2018
DOI: 10.4168/aair.2018.10.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Allergens From Black Tiger ShrimpPenaeus monodonThat Can Bind and Cross-link IgE by ELISA, Western Blot, and a Humanized Rat Basophilic Leukemia Reporter Cell Line RS-ATL8

Abstract: BackgroundBlack tiger shrimp Penaeus monodon is one of the common causes of shellfish allergy that is increasing worldwide. One of the important problems in the management of shellfish allergy is the lack of accurate diagnostic assay because the biological and immunological properties of allergens in black tiger shrimp have not been well characterized. This study aims to detect proteins with the ability to bind and cross-link immunoglobulin E (IgE) from black tiger shrimp by enzyme-linked immunosorbent assay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…The latter assay made use of a rat basophilic leukemia cell line transfected with human IgE receptor FcεRI and luciferase reporter gene (RS-ATL8) [54], which obviates the need for complicated procedures involving blood stimulation and flow cytometry-based analyses while keeping the benefits of measuring specific allergen-IgE crosslinking. A very recent study by Jarupalee et al [55] presented remarkable findings, where only the 38 kDa-and 115 kDa-shrimp protein fractions induced higher reporter signals in EXiLE test while fractions containing shrimp proteins of 19 kDa, 38 kDa, 41 kDa and 115 kDa displayed IgE reactivity in Western blot. The 115-kDa proteins indeed exhibited weak IgE reactivity but were capable of inducing sufficient IgE crosslinking.…”
Section: Diagnosis Of Shellfish Allergymentioning
confidence: 97%
“…The latter assay made use of a rat basophilic leukemia cell line transfected with human IgE receptor FcεRI and luciferase reporter gene (RS-ATL8) [54], which obviates the need for complicated procedures involving blood stimulation and flow cytometry-based analyses while keeping the benefits of measuring specific allergen-IgE crosslinking. A very recent study by Jarupalee et al [55] presented remarkable findings, where only the 38 kDa-and 115 kDa-shrimp protein fractions induced higher reporter signals in EXiLE test while fractions containing shrimp proteins of 19 kDa, 38 kDa, 41 kDa and 115 kDa displayed IgE reactivity in Western blot. The 115-kDa proteins indeed exhibited weak IgE reactivity but were capable of inducing sufficient IgE crosslinking.…”
Section: Diagnosis Of Shellfish Allergymentioning
confidence: 97%
“…The measurement of luciferase signal is thus theoretically reflecting the degree of IgE crosslinking. The utility of EXiLE was exemplified by the remarkable findings by Jarupalee et al [30] whom illustrated that only the 38 ]. Thirty-five shrimp allergic and tolerant subjects defined by DBPCFC were assessed in this study to compare the diagnostic accuracy of conventional SPT, shrimp extract and rPen a 1 sIgE measurement with BAT and EXiLE.…”
Section: Key Pointsmentioning
confidence: 99%
“…The measurement of luciferase signal is thus theoretically reflecting the degree of IgE crosslinking. The utility of EXiLE was exemplified by the remarkable findings by Jarupalee et al [30] whom illustrated that only the 38 kDa- and 115 kDa-shrimp protein fractions induced higher reporter signals by EXiLE test whereas fractions containing 19 kDa, 38 kDa, 41 kDa and 115KDa shrimp proteins fractions were IgE reactive in western blotting. The study data also showed that 115-kDa proteins were only weakly IgE positive by Western blot but could induce sufficient IgE crosslinking detectable by EXiLE test.…”
Section: Diagnosis Of Shellfish Allergymentioning
confidence: 99%
“…All the reagents for RS-ATL8 cell culture were procured from Gibco; ThermoFisher Scientific, USA. Measurement of luciferase activity was performed following the procedures described previously (Nakamura et al, 2012;Gericke et al, 2015;Jarupalee et al, 2018) with some modifications. Briefly, the RS-ATL8 cells were seeded at 5×10 4 cells per well in 96 wellplate (50 mL per well) and incubated for 3 h. Cells were then sensitized overnight with the pre-mixture of 5 mg/mL of human-IgE (Abcam, USA) and various concentrations (0.5-512 mg/mL) of plant-produced anti-human IgE (stock 3.4 mg/mL) or Omalizumab (stock 75 mg/mL) diluted in PBS, for 1 h at 37°C.…”
Section: Ige Cross-linking Induced Luciferase Expression Studymentioning
confidence: 99%